Ina-SASet: Dataset for Developing Indonesian Sentiment Lexicon for Extracting Consumer Preference Based on Fine Grained Sentiment Analysis Technique - Bagus Setya Rintyarna (International Journal of Intelligent Systems and Applications in Engineering, 2024)
We collect and build a database called Ina-SASet, i.e.: dataset for developing Indonesian sentiment Lexicon for extracting consumer Preference based on fine grained sentiment analysis technique. The dataset was gathered from Twitter from January 1st 2022 to December 31st 2022, since Twitter is a popular microblogging platform for obtaining huge repository. We used Twitter API by employing several related keywords to crawl the dataset from Twitter. As many as 121.327 was successfully grabbed from Twitter platform. We then text pre-processed the dataset by 1) splitting the dataset into sentence, 2) applying tokenizing to the split sentences, 3) removing stop word by using online stop word collection, 3) stemming the token by matching them with Kamus Besar Bahasa Indonesia (KBBI) online repository. The stemmed token was then saved into MySQL database. The creation of an Indonesian sentiment lexicon resource pertaining to consumer preference extraction would be aided by this endeavour.